2005
DOI: 10.1021/om050406q
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Reactions of Base-Free Bis(1,2,4-tri-tert-butylcyclopentadienyl)uranium Oxide, Cp‘2UO

Abstract: Reduction of the uranium metallocene, [η 5 -1,2,4-(Me 3 C) 3 C 5 H 2 ] 2

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

28
209
1
4

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 237 publications
(247 citation statements)
references
References 47 publications
(106 reference statements)
28
209
1
4
Order By: Relevance
“…shows the Me 3 C-groups in a 2:1 area ratio, but the Cp-ring CH groups are inequivalent, Table 1 rationalizes this behavior is that the uranium-oxygen bond is better represented by the polar resonance structure U + -O -, which emphasizes the electronegativity of the oxygen atom and therefore nucleophilicity, 14 whereas the uranium-nitrogen bond is better represented by the double bond resonance structure U=NMe, consistent with the lower electronegativity of the NMe group, and therefore lower nucleophilicity. These resonance structures emphasize the differences in local charges on the atoms in their ground states, but the general concept of atom electronegativity in conjugation with the electroneutrality principle 23 are qualitatively useful models that account for the reactivity Eisen, 10 and on the left hand side is a pathway originally suggested by Bergman for the catalytic reaction between (η 5 -C 5 H 5 ) 2 Zr(NHR) 2 and an acetylene, 26 which is adapted for the uranium metallocenes.…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…shows the Me 3 C-groups in a 2:1 area ratio, but the Cp-ring CH groups are inequivalent, Table 1 rationalizes this behavior is that the uranium-oxygen bond is better represented by the polar resonance structure U + -O -, which emphasizes the electronegativity of the oxygen atom and therefore nucleophilicity, 14 whereas the uranium-nitrogen bond is better represented by the double bond resonance structure U=NMe, consistent with the lower electronegativity of the NMe group, and therefore lower nucleophilicity. These resonance structures emphasize the differences in local charges on the atoms in their ground states, but the general concept of atom electronegativity in conjugation with the electroneutrality principle 23 are qualitatively useful models that account for the reactivity Eisen, 10 and on the left hand side is a pathway originally suggested by Bergman for the catalytic reaction between (η 5 -C 5 H 5 ) 2 Zr(NHR) 2 and an acetylene, 26 which is adapted for the uranium metallocenes.…”
Section: Resultsmentioning
confidence: 87%
“…14 In this paper, we show that the [η 5 -1,2,4-(Me 3 C) 3 C 5 H 2 ] 2 U fragment yields a monomeric methylimido derivative that undergoes irreversible cycloaddition reactions with internal acetylenes. In addition, we report that the less heavily substituted derivatives derived from 1,3-(Me 3 E) 2 C 5 H 3 (E = C, Si) do not yield monomeric imido metallocenes.…”
Section: Introductionmentioning
confidence: 79%
“…This is followed by a step in which CH 2 inserts into H 2 and Cp 2 CeX by cleavage of the C-X bond. Experimental evidence for the two-step mechanism was derived by observing that (a) the Me 3 C-groups on the Cp'-rings can act as an intramolecular trap for CH 2 , when H 2 is absent, as can added cyclohexene, which formed norcarane, and cyclohexane-d 12 solvent, which formed methylcyclohexane-d 12 , (b) NMR evidence was obtained for Cp' 2 CeCH 2 X, X = Cl, Br, I and (c) when X = OMe, Cp' 2 Ce(η 2 -CH 2 OMe) was isolated. 1,4 Thus, the combined computational and experimental studies showed that the two-step pathway 5 proceeding by way of a carbenoid intermediate is general for the CH 3 X derivatives studied.…”
Section: Introductionmentioning
confidence: 99%
“…The bis(cyclopentadienyl) complexes of uranium (C 5 Me 4 R) 2 UX 2 (R = Me or Et; X = Cl or I) [1][2][3], (1,3-R 1 2 C 5 H 3 ) 2 UX 2 and (1,2,4-R 1 3 C 5 H 3 ) 2 UX 2 (R 1 = t Bu, SiMe 3 ; X = Cl, I) [4][5][6][7] have been known for years, owing to the ease of preparation of reliable chloride and iodide starting materials. With the vast amount of literature attention devoted to (C 5 Me 4 R)UX 2 compounds, it is curious that the corresponding bis(cyclopentadienyl) uranium bromide systems have not been investigated to a similar extent.…”
Section: Introductionmentioning
confidence: 99%
“…An alternative method that has been employed to prepare uranium(IV) bromide complexes is halide exchange. For example, (1,2,4-t Bu 3 C 5 H 2 ) 2 UBr 2 (16) [5] and (1,3-R 2 C 5 H 3 ) 2 UBr 2 (R = SiMe 3 (17), t Bu (18)) [4] were prepared by reacting the chloride analogues with excess Me 3 SiBr, and (17) from its chloride analogue and BBr 3 [7].…”
Section: Introductionmentioning
confidence: 99%